Enhancing The Loyalty of Credit Guarantee Corporation Partners Through Service Quality, Facilities, Prices, and Accessibility - Sakinah, Tazkiyah; Banuwa, Laili Fadhila; Nugroho, Dwi; Putri, Lidya Ayuni (International Journal of Economics, Business, and Entrepreneurship, 2024)
This study aims to analyse the effect of service quality, facilities, price, and accessibility on the loyalty of credit guarantee partners on the Sumatra island. The research method is quantitative, using descriptive analysis and multiple linear regression. Primary data was obtained through questionnaires distributed to 135 credit guarantee partners, while secondary data was obtained from various sources relevant to the research. The results of the multiple regression analysis show that the four variables simultaneously have a significant effect on partner loyalty. However, only facilities and prices partially have a positive and significant effect. Accessibility had a significant negative effect, while service quality had no significant effect. These findings suggest that improved facilities and competitive pricing are key to increasing guarantor partner loyalty. This research has important implications for bonding companies in formulating strategies to maintain and increase partner loyalty.